2017
DOI: 10.1097/mao.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

The Normal Adult Human Internal Auditory Canal: A Volumetric Multidetector Computed Tomography Study

Abstract: IAC volumes of normal adult subjects, measured by CT, were larger in males and not significantly different with respect to age or laterality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This is in accordance to previous studies, which reported a mean IAC diameter between 5 and 6 mm and an IAC diameter range between 2 and 8 mm to be normal [ 15 , 17 , 29 , 30 ]. In contrast, only few previous studies reported volumetric data on a normal IAC [ 31 ]. Furthermore, information on volumes of hypoplastic IAC as well as IAC size in IEM is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance to previous studies, which reported a mean IAC diameter between 5 and 6 mm and an IAC diameter range between 2 and 8 mm to be normal [ 15 , 17 , 29 , 30 ]. In contrast, only few previous studies reported volumetric data on a normal IAC [ 31 ]. Furthermore, information on volumes of hypoplastic IAC as well as IAC size in IEM is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the radiological assessment of such processes, it would seem more desirable to have a reproducible quantifiable objective measure of the IAC rather than relying on the subjective impression of IAC asymmetry or unidimensional measurements of the acoustic pore. Such a quantitative measure could also serve as a baseline for subsequent comparisons when monitoring a disease process (15). For this reason, we evaluated morphometry, angles, and volume of IAC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the developments in radiological imaging techniques in recent years, imaging methods such as magnetic resonance imaging (MRI) and computed tomography (CT) are used extensively to elucidate the anatomy of IAC (7, 13 -16). It was determined that the studies using CT or MRI in the literature are related to the distance of IAC to various parts of the temporal bone, length of canal, diameters of IAP and shapes of IAC (4,6,7,15,17). When the literature studies were examined, we believe that there is a great need a study with more comprehensive, more organized and including more parameters related to IAC.…”
Section: Introductionmentioning
confidence: 99%
“…2) A recent study of computed tomography (CT) scans of the IAC found that the median IAC volume of adults was 191 mm 3 and 202 mm 3 in the right and left ears respectively, including both sexes. 8 Additionally, a study of sporadic non-NF2 intracanalicular tumors found that AHDR was higher in tumors that had a growing IAC component. 14…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that internal auditory canal (IAC) tumor volume > 200 mm 3 would be associated with the development of hearing loss based on a study which indicated median internal auditory canal (IAC) volume of adults ranged between 191 and 202 mm 3 on computerized tomography (CT) scan. 8 Understanding the relationship of these audiometric and imaging characteristics with hearing loss may be useful in predicting which patients are at risk of developing significant hearing loss over time and therefore help guide the decision to offer future intervention.…”
Section: Introductionmentioning
confidence: 99%